David and Goliath : underdogs, misfits, and the art of battling giants - Gladwell, Malcolm, 1963- (Little, Brown and Company, 2013)
Drawing upon examples from the world of business, sports, culture, cutting-edge psychology and an array of unforgettable characters around the world, the author of The Tipping Point, Blink and Outliers looks at the complex and surprising ways in which the weak can defeat the strong, how the small can match up against the giant, and how our goals (often culturally determined) can make a huge difference in our ultimate sense of success.